Program Kaliber (Kawal Pemilu Bersih) Di Kelurahan Koto Panjang Kota Padang Panjang - Rachma, Aryo Yasya; Sukmareni, Sukmareni (LPPM Universitas Dehasen Bengkulu, 2024)
This research aims to analyze the Clean Election Guard Program implemented in Koto Panjang Subdistrict, Padang Panjang Timur District, Padang Panjang City which focuses on discussing the form of socialization carried out and the obstacles encountered in guarding the 2024 Election. The research method used is field research with a qualitative approach. Data sources include primary data sources obtained directly from the field and secondary data sources from books, journals and scientific articles. Data collection techniques were carried out using interviews and documentation. The collected data was then analyzed using qualitative data analysis methods. The results of this research conclude that the Clean Election Guard (Kaliber) Program in Koto Panjang Subdistrict, Padang Panjang Timur District, Padang Panjang City has been running effectively and efficiently in accordance with the desired objectives, namely to oversee the implementation of the 2024 Election which is honest, fair, clean and democratic.